2002
DOI: 10.1136/jme.28.5.313
|View full text |Cite
|
Sign up to set email alerts
|

Why we should not seek individual informed consent for participation in health services research

Abstract: Ethics committees now require that individuals give informed consent to much health services research, in the same way as for clinical research. This is misguided. Existing ethical guidelines do not help us decide how to seek consent in these cases, and have allowed managerial experimentation to remain largely unchecked. Inappropriate requirements for individual consent can institutionalise health inequalities and reduce access to services for vulnerable groups. This undermines the fundamental purpose of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 23 publications
(11 reference statements)
1
68
0
1
Order By: Relevance
“…Data protection legislation prevented researchers from accessing names and addresses of potential participants, so staff in each general practice had to generate the randomised mailings. This proved prohibitively expensive Estimate recruitment and retention rates The feasibility study showed that recruitment rates in the current ethical and legal framework might make a definitive trial difficult 27 Calculate sample sizes A small scale feasibility study in 3 general practices informed sample size calculation for a definitive trial using both cluster and individual randomisation based on rates of acceptance of screening have not been obtained during prior research with the target group, a feasibility study may be needed to model patient flow. Such studies also enable assessment of feasibility of the methods of randomisation including acceptability to participants and suitable level to avoid contamination effects.…”
Section: Key Task Examplementioning
confidence: 99%
“…Data protection legislation prevented researchers from accessing names and addresses of potential participants, so staff in each general practice had to generate the randomised mailings. This proved prohibitively expensive Estimate recruitment and retention rates The feasibility study showed that recruitment rates in the current ethical and legal framework might make a definitive trial difficult 27 Calculate sample sizes A small scale feasibility study in 3 general practices informed sample size calculation for a definitive trial using both cluster and individual randomisation based on rates of acceptance of screening have not been obtained during prior research with the target group, a feasibility study may be needed to model patient flow. Such studies also enable assessment of feasibility of the methods of randomisation including acceptability to participants and suitable level to avoid contamination effects.…”
Section: Key Task Examplementioning
confidence: 99%
“…However, where capacity is an issue, this may not be the case and safeguards are important to protect participants, although it can also be argued that there needs to be greater attention paid to facilitating the involvement of seldom heard groups in research, and promoting decision-making where possible (see Parker et al, 2011;. Cassell and Young (2002) would refine the focus of ethical review still further, arguing that informed consent is important in clinical research but misses the point in broader policy and practicebased health services research. They suggest, rather than individual informed consent, there needs to be an on-going contract of evaluation and development based on practice.…”
Section: The Development Of Research Ethical Scrutinymentioning
confidence: 99%
“…by failing to account for the impact of zero-hours contracts on ability to access services). This may lead to the development of interventions which are doomed to low impact or failure for the most vulnerable in society (Cassell and Young, 2002), increasing the deleterious effects of health inequalites.E.g.if zero-hours contracts do impact on sexual health service access then interventions to improve access which do not address or account for this, will do little to improve access for those negatively impacted in this way. Non-critical enquiry may also reinforce moral positions which are victim-blaming (Lupton, 1993).…”
Section: Key Aims For a Critical Epidemiology For Sexual Healthmentioning
confidence: 99%